Prophecy in an African Context: Methodological Considerations - Bishau, David (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
Efforts to view prophecy from an African perspective fall into the category of approaches to the Bible that seek to make the Bible meaningful to the world or horizon of the reader. Basically, these are efforts that seek to contextualize the Bible. Concerns to contextualize the Bible so that it speaks to the context of the reader, and in our case, the African context, are not new. There has been a long standing debate reviewing the movement in biblical interpretation dubbed ‘the New Hermeneutic’ whose major concerns were to apply the biblical text to the context of the reader and in a way that incorporated the culture of the reader. Our thesis in this chapter is that while the concerns are novel and indeed genuine, scholars who venture in these endeavours have not always been forthcoming in terms of how they propose to contextualize the Bible in ways that restrain biblical interpretation from falling back to, and into, the methodological pitfalls of the past, especially the pitfalls of the various shades and forms of eisegesis whose major heuristic crime was the failure to do enough justice to the text. In this chapter we revisit the history of the interpretation of the Bible in general, and prophecy in Ancient Israel in particular, in a bid to make our own proposal on the method and, or, hermeneutics that are appropriate to interpret the prophetic books in an African context but still doing justice to the message that was intended by the authors of the texts to the audiences of their time. We propose a fresh look at hermeneutics as a generic term that distinguishes it from exegesis and incorporates principles of cultural relativism and social scientific criticism. We very briefly apply the social scientific conceptual metaphor of social capital as a demonstration of the application of our hermeneutics to understand the prophet Isaiah and selected contemporary prophets in Zimbabwe.
free